"I was trying to speak to their human side" coping responses of Belgium's undocumented migrants to barriers in health-care access. Issue 3 (15th September 2020) - Lafaut, Dirk; Coene, Gily
Abstract : Purpose: Undocumented migrants experience major legal constraints in their health-care access. Little is known on how undocumented migrants cope with these limitations in health-care access as individuals. The purpose of this study is to explore the coping responses of undocumented migrants when they experience limited health-care access in face-to-face encounters with health-care providers. Design/methodology/approach: The authors conducted multi-site ethnographic observations and 25 semi-structured in-depth interviews with undocumented migrants in Belgium. They combined the "candidacy model" of health-care access with models from coping literature on racism as a framework. The candidacy model allowed them to understand access to health care as a dynamic and interactive negotiation process between health-care workers and undocumented migrants. Findings: Responses to impaired health-care access can be divided into four main strategies: (1) individuals can react with a self-protective response withdrawing from seeking further care; (2) they can get around the obstacle; (3) they can influence the health-care worker involved by deploying discursive or performative skills; or (4) they can seek to confront the source of the obstacle. Research limitations/implications: These findings point to the importance of care relations and social networks, as well as discursive and performative skills of undocumented migrants when negotiating barriers in access to health care. Originality/value: This study refines the candidacy model by highlighting how individuals respond on a micro-level to shifts towards exclusionary health policies and, by doing so dynamically, change provision of health-care services.